SpaceOps 2010 Conference 2010
DOI: 10.2514/6.2010-2208
|View full text |Cite
|
Sign up to set email alerts
|

Housekeeping Data: Can You Afford Not to Compress It?

Abstract: Previous work at ESA/ESOC showed that spacecraft housekeeping telemetry contains significant amounts of information redundancy. A simple algorithm was proposed that removed this redundancy almost as effectively as well known commercial products like zip. However conventional wisdom says that even if stored housekeeping telemetry can be compressed -it should not be. At first glance the arguments appear reasonable; it would reduce the robustness of the ground space link, it would make using existing infrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In [6], bitwise exclusive-or (XOR) operations are applied periodically within the group, and then a modified version of run-length encoding (RLE) is proposed to encode the resulting data. In [1], [3], it is shown that lossless compression methods such as Lempel-Ziv (LZ) and RLE yield significantly better compression results when applied to individual bit positions across several data packets. In [4], groups are dynamically created based on a similarity metric, and then the differences between consecutive packets in a group are coded with either RLE or LZ.…”
Section: Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…In [6], bitwise exclusive-or (XOR) operations are applied periodically within the group, and then a modified version of run-length encoding (RLE) is proposed to encode the resulting data. In [1], [3], it is shown that lossless compression methods such as Lempel-Ziv (LZ) and RLE yield significantly better compression results when applied to individual bit positions across several data packets. In [4], groups are dynamically created based on a similarity metric, and then the differences between consecutive packets in a group are coded with either RLE or LZ.…”
Section: Previous Workmentioning
confidence: 99%
“…This is analogous to [8], which interleaves the transmission of packet differences and full packet contents. In terms of resiliency to data loss events -but not realtime transmission capabilities-, periodically transmitting full reference packets is roughly equivalent to [1], [3], [4], [6], [17], [18] when packets are divided in groups and compressed separately. The effect on compression efficiency of periodically activating both the full mask and uncompressed flags is analyzed in Section IV-D.…”
Section: ) Full Mask and Uncompressed Packet Flagsmentioning
confidence: 99%
See 2 more Smart Citations